Review of oritavancin for the treatment of acute bacterial skin and skin structure infections - Ana Alejandra García Robles; Eduardo López Briz; María Dolores Fraga Fuentes; Rocío Asensi Diez; Jesús Francisco Sierra Sánchez (Farmacia Hospitalaria)
Objective: To assess critically oritavancin, a second-generation lipoglycopeptide, for the treatment of Acute Bacterial Skin and Skin Structure Infections caused by susceptible Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus. Method: An evaluation report of oritavancin in Acute Bacterial Skin and Skin Structure Infections was carried out according to the methodology of the Group for drug evaluation, standardization and research in drug selection of the Spanish Society of Hospital Pharmacy (SEFH)1, with the MADRE 4.0 program. A search was made in PubMed, in the web www.clinicaltrials. gov, Embase, PubMed and UptoDate. The European Medication Agency and Food and Drug Administration evaluation reports were also used. Results: Single-dose oritavancin demonstrated its non-inferiority efficacy versus vancomycin in Acute Bacterial Skin and Skin Structure nfections, with a similar safety profile. Its potential advantage over other therapeutic alternatives lies in its administration in single dose and in its no need for plasma levels monitoring, which would allow its administration on an outpatient basis. Regarding to the other alternative possibilities of oral (linezolid, tedizolid) or IM (teicoplanin) treatment, oritavancin would improve the adherence to the treatment. Although oritavancin could be more efficient in certain scenarios (outpatient treatment versus inpatient treatment with alternatives), there are no convincing studies in this regard so far. On the other hand, alternative drugs above-mentioned, can also allow outpatient treatment, reducing advantages of oritavancin and further increasing cost differences. Therefore, given that the efficacy is similar to the alternatives, a cost minimization analysis could be considered. Conclusions: Oritavancin is comparable in terms of efficacy and safety to the existing alternatives in Acute Bacterial Skin and Skin Structure Infections, without improvements in the cost-effectiveness ratio, because of the proposed positioning is to consider it for the treatment of vancomycinresistant enterococcal infection in adult patients when the use of linezolid or tedizolid is contraindicated.